Alternative Risk Measurement Methods: Theoretical Aspects of the Margin of Safety - Brazauskas, Martynas (Socialiniai tyrimai, 2016)
Investment risk measurement using only quantitative methods does not always work properly measuring risk and avoiding losses. In order to effectively measure and reduce risk it is appropriate to use alternative methods for risk measurement. This paper discusses the safety limit, which applies as the method of risk measurement and reduction. Review of empirical studies has shown that B. Graham’s proposed fundamental criteria to measure and reduce risk improve investment portfolio returns and efficiency.
Keywords: margin of safety; value investing; investment risk; stocks